Notes on the Pselaphinae (Coleoptera: Staphylinidae) in Shanghai, China - Yin, Zi-Wei; Jiang, Ri-Xin; Chen, Zhi-Bing (Zootaxa, 2017)
Four pselaphine species are reported to occur in Shanghai, all belonging to the tribe Batrisini. A new species, Batriscenellus xijiaogongyuan sp. n., is described based on the material collected at the Shanghai Zoo. New distributional or collecting data for three species, i.e. Batrisodes sibiricus Sharp, Physomerinus pedator (Sharp), and Batriscenellus orientalis (Löbl), are provided.